CMS Outer Tracker Phase-2 Upgrade module noise and mitigation. (1st December 2022) - Zografos, A.; Blanchot, G.; Kovacs, M.; Maier, S.; Mateos, I.; Pauls, A.; Schleidweiler, K.
Abstract: The CMS Outer Tracker phase-2 upgrade silicon modules are required to reach noise levels close to the ones expected from the analogue front-end attached to an ideal pixel/strip. Module prototypes, featuring the latest and final prototype hybrids before the production, showed noise that was higher than the expected which could pose a problem in terms of achieving the hit efficiency target. Investigations, reveal the failure modes which are modelled in order to guide mitigation tweaks for the production designs. Knowledge acquired from the investigations along with the noise mitigation design changes implemented on the production hybrids are presented.